Relanzamiento de la marca peruana de ropa femenina Maxia: manual de identidad visual y aplicación de estrategia en Instagram - Goicochea Ortiz, Ximena Alessandra (2021)
This paper will detail how the relaunch of the Peruvian women's clothing brand “Maxia” will take place, in which the brand will make a 180-degree turn, from branding to style and quality of each garment. This objective will be achieved by attracting and retaining new customers, to whom we will show a line of timeless clothing in order to place ourselves in their top of mind. In addition, we will establish a cost-benefit relationship, justified in the quality of our garments that will meet and / or exceed the expectations of our customers. We are committed to being a brand that combines comfort with versatility and elegance from garments with simple designs that can be adapted to the personality and needs of the end consumer, betting on a new image that will reveal these qualities. Once "Maxia" is positioned in the virtual fashion market in Peru, it will seek to reach more people through physical stores and the creation of a website that allows us to make international shipments.